Pengaruh Aromaterapi Lavender terhadap Tingkat Kecemasan pada Ibu Nifas - Yustika, Made Dwiana Pradnya; Karuniadi, I Gusti Agung Manik; Saraswati, Putu Ayu Dina (ProHealth Journal, 2025)
The postpartum period is the most critical period in the life of mother and baby. Complaints that often arise in mothers with postpartum anxiety are feeling anxious, worried about her the condition and the baby, having sleep disorders, concentration disorders, feeling afraid of being alone. Postpartum maternal anxiety is measured using the DASS questionnaire sheet. Management that can be done to overcome this is by providing Lavender Aromatherapy. This research design is Pre-Experimental through One Group Pretest-Postest Design. The number of samples is 30 postpartum mothers with Non-Probability Sampling sampling technique, Purposive Sampling type. Data were analyzed using the Wilcoxon test to determine the difference in anxiety levels before and after being given lavender aromatherapy. Description of postpartum maternal anxiety before being given lavender aromatherapy at Bhayangkara Hospital, namely from a total of 30 respondents, most of the respondents before being given Lavender aromatherapy experienced moderate anxiety, namely 28 respondents (93.3%). The average level of maternal anxiety was 11.37. After the intervention, most of the respondents, namely 23 people (76.7%), were in the mild anxiety category. The average level of anxiety after the intervention was 8.53. Based on the results of the Wilcoxon calculation, a p value of 0.000 <0.05 was obtained, meaning that there is an effect of Lavender Aromatherapy on the level of anxiety in postpartum mothers at Bhayangkara Hospital, Denpasar. Health workers, especially midwives, can begin to integrate aromatherapy into postnatal care practices as a safe, inexpensive, and easy-to-apply supporting intervention.